Decreased default-mode network homogeneity in unaffected siblings of schizophrenia patients at rest - Guo, Wenbin; Liu, Feng; Yao, Dapeng; Jiang, Jiajing; Su, Qinji; Zhang, Zhikun; Zhang, Jian; Yu, Liuyu; Zhai, Jinguo; Xiao, Changqing (Psychiatry research. Neuroimaging, 2014)
The dysconnectivity hypothesis proposes that abnormal resting state connectivity within the default-mode network (DMN) plays a key role in schizophrenia. Little is known, however, about alterations of the network homogeneity (NH) of the DMN in unaffected siblings of patients with schizophrenia. Unaffected siblings have unique advantages as subjects of neuroimaging studies independent of the clinical and treatment issues that complicate studies of the patients themselves. In the present study, we investigated NH of the DMN in unaffected siblings of schizophrenia. Participants comprised 46 unaffected siblings of schizophrenia patients and 50 age-, sex-, and education-matched healthy controls who underwent resting state functional magnetic resonance imaging (fMRI). Automated NH and group independent component analysis (ICA) approaches were used to analyze the data. Compared with healthy controls, the unaffected siblings of schizophrenia patients showed decreased DMN homogeneity in the left precuneus. No significantly increased DMN homogeneity was found in the sibling group relative to the control group. Our results suggest that there is decreased NH of the DMN in unaffected siblings of schizophrenia patients and indicate that the alternative perspective of examining the DMN NH in patients׳ siblings may improve understanding of the nature of schizophrenia. •Little is known about the alterations of the DMN NH in schizophrenia siblings.•Unaffected siblings have unique advantage independent of clinical and treatment issues.•NH was used to investigate the network homogeneity of the DMN in siblings.•We introduce an alterative perspective of examining the DMN NH in the siblings.